Vocational Training of IT-Professionals : coping with future demands - Schwarz, Henrik [Verfasser]; Conein, Stephanie [Verfasser] (My University, 2017)
"Since their implementation in 1997 the four German training occupations in the field of information and communication technology are writing a success story. Nevertheless they are facing; big challenges because of the rapid development of technology and the increasing digitalization of production, service and consumption. The German Federal Institute for Vocational Education and Training (BIBB) has evaluated the existing IT-training occupations. The results are based on a broad survey conducting interviews ln companies 'With different target groups combined with an online questioning of more than 6,000 participants. Findings suggest that although there is a common contentment among companies, trainers and Trainees, new contents should be included in the training and the training profiles as well as their inner structure should be revised." (authors' abstract; BIBB-Doku)
Keywords: S 6.4.9 IT-Berufe; G 2.2.1 Technologisierung; L 6.2.3 Evaluation; IT-Beruf; Evaluation; Ausbildungsinhalt